Implementation of a system for the management and control of the application process of foreign students - Berrios Guevara, Yéiner Michael (2015)
In this research has done a web system that has been called INTERSYS, using agile development methodology Scrum, with the aim of measure the level of satisfaction of foreign students in the process of aplication for an exchange in la Universidad Católica Santos Toribio de Mogrovejo (USAT). The population was integrated of foreign students who took undergraduate studies at the USA since 2013-I until 2014-II. The research is quantitative. Which have a design pre experimental of type pre and post test with an only group? To the students of exchange and staff of the office of international relations was applied an initial questionnaire to determine the perception on the current application process. Then, the study population received encouragement using INTERSYS, and then applies a final questionnaire to measure the level of satisfaction using the developed system. With this study we can know that 100% of students prefer INTERSYS with respect to current procedure, the same way expressed their complete satisfaction with system characteristics, most notably the integration of the application procedure with tuition. International relations staff agrees that INTERYS accelerates the processes of receiving application formats, manage acceptance and enrollment of students.